2016
DOI: 10.1016/j.bjm.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory viruses in shelter dogs maintained under varying environmental conditions

Abstract: Three dog shelters in Rio Grande do Sul were investigated for associations between the occurrence of respiratory viruses and shelter environmental conditions. Nasal secretions randomly collected during the cold season were tested via PCR, and this data collection was followed by nucleotide sequencing of the amplicons. In shelter #1 (poor sanitary and nutritional conditions, high animal density and constant contact between dogs), 78% (58/74) of the nasal samples were positive, 35% (26/74) of which were in singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
4
19
2
Order By: Relevance
“…Most of the dogs in that study were reportedly vaccinated against CDV, but had likely not received a full course of vaccination (Calderon et al 2007) [EB1]. Other studies confirm that CDV is present in Brazil (Budaszewski et al 2014, Monteiro et al 2016, Alves et al 2018), Chile (Acosta-Jamett et al 2011, Colombia (Espinal et al 2014), Cuba (González-Chávez et al 2017), Ecuador (DiGangi et al 2019 including the Galápagos Islands (Levy et al 2008 (Gizzi et al 2014) [EB1]. Other studies show that CPV2 is present in Argentina (Calderón et al 2011(Calderón et al , 2015, Brazil (Alves et al 2018, Headley et al 2018, Chile (Acosta-Jamett et al 2015), Colombia (Duque-García et al 2017), Cuba (Pino-Rodríguez et al 2018), Ecuador (Levy et al 2008, Aldaz et al 2013, De la Torre et al 2018, DiGangi et al 2019, Mexico (Ortega et al 2017) and Uruguay (Pérez et al 2007, Puentes et al 2012, Maya et al 2013 [EB1].…”
Section: Canine Distemper Virusmentioning
confidence: 92%
See 1 more Smart Citation
“…Most of the dogs in that study were reportedly vaccinated against CDV, but had likely not received a full course of vaccination (Calderon et al 2007) [EB1]. Other studies confirm that CDV is present in Brazil (Budaszewski et al 2014, Monteiro et al 2016, Alves et al 2018), Chile (Acosta-Jamett et al 2011, Colombia (Espinal et al 2014), Cuba (González-Chávez et al 2017), Ecuador (DiGangi et al 2019 including the Galápagos Islands (Levy et al 2008 (Gizzi et al 2014) [EB1]. Other studies show that CPV2 is present in Argentina (Calderón et al 2011(Calderón et al , 2015, Brazil (Alves et al 2018, Headley et al 2018, Chile (Acosta-Jamett et al 2015), Colombia (Duque-García et al 2017), Cuba (Pino-Rodríguez et al 2018), Ecuador (Levy et al 2008, Aldaz et al 2013, De la Torre et al 2018, DiGangi et al 2019, Mexico (Ortega et al 2017) and Uruguay (Pérez et al 2007, Puentes et al 2012, Maya et al 2013 [EB1].…”
Section: Canine Distemper Virusmentioning
confidence: 92%
“…A study conducted in three shelters in the South of Brazil showed, by PCR from nasal swabs, that CAV2 was present as a single infection in 5.4 and 7.8% of the dogs in two shelters, while canine parainfluenza virus (CPiV; parainfluenza virus type 5) was found in 29.7 and 8.6% of the dogs, respectively. CAV2 was present as a coinfection with CDV in 2.7% of the dogs, CAV2 with CPiV in 22.9% of the dogs, CPiV and CDV in 4% of the dogs and CAV2, CDV and CPiV in 13.5% of the dogs in one of the shelters (Monteiro et al 2016) [EB1].…”
Section: Canine Infectious Respiratory Disease Complexmentioning
confidence: 99%
“…Its horizontal transmission can occur due to direct or indirect contact between dogs. This contact can happen through nasal secretions, semen and contaminated aerosols, regardless of sex or age distinction, being observed an increased susceptibility in puppies less than 2 months [63]. Animals without updated immunization record, with vaccination failures and maternal immunization also become more prone to infection [64].…”
Section: Viral Diseases 41 Canine Herpesvirusmentioning
confidence: 99%
“…With the collection of the appropriate material, histopathological tests, biochemical, immunofluorescence microscopy and molecular tests can be performed. The CHV-1 presence can be confirmed in samples by polymerase chain reaction [63] and by the sequencing, comparing similarity between the surrounding sequences. PCR allows for viral detection even in animals that have the latent infection [58].…”
Section: Viral Diseases 41 Canine Herpesvirusmentioning
confidence: 99%
See 1 more Smart Citation